SOMATOTROPIN LEVEL IN LONG-TERM ANTIHYPERTENSIVE TREATMENT - I. I. Mustafayev (Российский кардиологический журнал, 2003)
Changes in plasma STH in long-term (12 months) drug treatment of essential hypertension (EH) with Nadolol, Propranolol, Prazosine, Hydrochlorothiazide have been studied in 104 men with EH II degree according to the WHO classification. Treatment with Propranolol and Nadolol led to increased plasma STH in the first 2 months of treatment, particularly in subjects with baseline increase and long-term history of EH. Mean plasma STH levels decrease to a greater extent with increasing duration of drug intake. Treatment with hydrochlorothiazide is generally accompanied by no relaible shift in plasma STHlevel, but may lead to increased plasma STH level in young subjects (below 50years of age).